“Serve and Ngalap berkah”: Motivation to be An Islamic Boarding School Teacher - Najib, Khotim Hanifudin; Mushodiq, Muhamad Agus; Widayat, Prabowo Adi; Djufri, Elyas (12 Waiheru, 2024)
Many studies have been conducted in various countries exploring why people become school teachers. However, only some have explored why someone becomes an Islamic boarding school teacher. This article explores why someone is becoming a teacher at an Islamic boarding school. This case study research was conducted by interviewing teachers at the Nurul Ummah Islamic Boarding School in Yogyakarta. A total of 8 teachers shared their experiences while being teachers at the Islamic boarding school. The research results show that teachers teaching at Islamic boarding schools are motivated to serve and "ngalap berkah." Serving has become a tradition for students who have completed their studies at Islamic boarding schools as a form of reciprocation of a student's gratitude to the Islamic boarding school and its Kyai. Ngalap berkah is believed to be a guarantee from the Kyai for the blessings of knowledge obtained by the students who become teachers at the Islamic boarding school.